The Effect Of The Implementation Of Professional Ethics And Competence On The Accuracy Of Giving Auditor Opinions (Empirical Study at Public Accountant Office (PAO) In Bandung) - Rahman, Erpi; Adinegara, Ahmad Andy; Nurfajar, Reja (Journal of Business, Accounting and Finance, 2025)
Auditor is a profession of a person who has certain qualifications, where in the performance of his duties, the auditor is required to conduct an audit in accordance with the audit procedures performed. This study aims to determine and examine the effect of the implementation of professional ethics and competence on the accuracy of giving auditor opinions in the public accounting firm in Bandung. This study uses a quantitative approach because the symptoms of observations are converted into numbers that are analyzed using statistics. The population in this study were all auditors who worked at the Public Accounting Firm in Bandung using the purposive sampling method and amounted to 9 PAF. The data analysis technique used is multiple linear regression analysis. The results of this study show that the contribution of professional ethics and competence to the accuracy of the auditor's opinion is 77.5%. Furthermore, based on the results of hypothesis testing, it can be seen that the Sig. value of the Professional Ethics variable is 0.001 <0.05 and the t_count value is 3.470> 2.028. Thus, the professional ethics variable has a positive and significant effect on the accuracy of the auditor's opinion. Meanwhile, the Sig. value of the Competency variable is 0.005 <0.05 and the t_count is 2.976> 2.028. Thus, it can be concluded that the Competency variable has a positive and significant effect on the accuracy of auditor opinions. At the same time, professional ethics and competence have a positive and significant effect on the accuracy of the auditor's opinion.